Intended location for Flora Fountain - Ghosh, Ayan (2023)
A stone statue stands at the centre of the roundabout inside Jijamata Udyan, which was chosen as the original installation site for the Flora Fountain, originally commissioned by the Agri Horticultural Society of Western India. However, the site was later changed and the fountain was placed at Churchgate, where it stands now.